Colon Epithelial MicroRNA Network in Fatty Liver - Paule V. Joseph; Sarah K. Abey; Dan Wang; Nicolaas H. Fourie; Natnael D. Kenea; Tatyana G. Vishnyakova; Jeffrey M. Robinson; Kristen R. Weaver; Christina M. Boulineaux; Hannah R. Davidson; LeeAnne B. Sherwin; Onyinyechi Ozoji; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background & Aims. Intestinal barrier alterations are associated with fatty liver (FL) and metabolic syndrome (MetS), but microRNA (miR) signaling pathways in MetS-FL pathogenesis remain unclear. This study investigates an epithelial-focused miR network in colorectal cell models based on the previously reported MetS-FL miR trio of hsa-miR-142-3p, hsa-miR-18b, and hsa-miR-890. Methods. Each miR mimic construct of MetS-FL miR trio was transfected into human colorectal cells, CRL-1790 or Caco-2. Global miRNome changes posttransfection were profiled (nCounter® Human v3 miRNA, NanoString Technologies). Changes in barrier (transepithelial electrical resistance, TEER) and epithelial cell junction structure (Occludin and Zona Occludens-1/ZO-1 immunofluorescence staining-confocal microscopy) were examined pre- and posttransfection in Caco-2 cell monolayers. A signaling network was constructed from the MetS-FL miR trio, MetS-FL miR-induced colorectal miRNome changes, ZO-1, and Occludin. Results. Transfection of CRL-1790 cells with each MetS-FL miR mimic led to global changes in the cellular miRNome profile, with 288 miRs being altered in expression by more than twofold. Eleven miRs with known cytoskeletal and metabolic roles were commonly altered in expression by all three miR mimics. Transfection of Caco-2 cell monolayers with each MetS-FL miR mimic induced barrier-associated TEER variations and led to structural modifications of ZO-1 and Occludin within epithelial cell junctions. Pathway analysis incorporating the MetS-FL miR trio, eleven common target miRs, ZO-1, and Occludin revealed a signaling network centered on TNF and AKT2, which highlights injury, inflammation, and hyperplasia. Conclusions. Colon-specific changes in epithelial barriers, cell junction structure, and a miRNome signaling network are described from functional studies of a MetS-FL miR trio signature.